Analisis Usia Arrester Akibat Gangguan Sambaran Langsung Petir Pada Transmisi 150 KV - Fathir Juliando; Iswadi Hasyim Rosma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Lightning strike is one of the main causes of faults at 150 kV transmission line in Indonesia. This fault may cause damage on the electrical system equipment. Therefore, the protection device to protect the equipment is essential to ensure reliable operation of electrical system. Arrester is a protection device that can be used to protect equipment from lighting strike. The life time of the arrester is effected, when the number of strike is increased. Therefore, the objective of this study is to analyze the lightning strike to the life time of the arrester. A number of parameters were used in this study such as: Thunderstormday (IKL),lightning current, the length of transmission line, The Total Probability of the Arrester Failure. It has been found from the results that when there was a lighting strike with 1 kA until 45 kAand the tail duration 0 until 45s , The Total Probability of the Arrester Failure is 0,00141255. Therefore, with IKL 150 per year, the life time of the arrester is 2 years and 2 months when it is hitted by 1 kA until 45 kA lighting.Keywords: Arrester, life time of arrester, lightning strike.